Marcelino García Flamenco: El maestro salvadoreño que dio su vida por las libertades de Costa Rica - Rodríguez Argüello, Percy K. (2019)
The pillars of the Costa Rican Foreign Policy, rest on a series of values, which are rooted in national identity and are intimately related to facts of history, which permeated national thinking. This article seeks to generate an approach to the life of Salvadoran teacher Marcelino García Flamenco, who in the context of the struggle against the Tinoco dictatorship in Costa Rica (1917-1919), gave his life for democracy and for Costa Rican freedoms, cultivating the idea of the teacher opposed to the army. For this, this research uses historical sources from the period between 1917 and 1924.